2021
DOI: 10.2147/ijgm.s302012
|View full text |Cite
|
Sign up to set email alerts
|

ARRDC3 as a Diagnostic and Prognostic Biomarker for Epithelial Ovarian Cancer Based on Data Mining

Abstract: The dysregulation of arrestin domain containing 3 (ARRDC3) has an important effect on oncogenesis and tumor progression in many cancers, including renal cell carcinoma and breast cancer. However, the role of ARRDC3 in ovarian cancer (OC) has not been reported. Methods: The present study explored the diagnostic and prognostic roles of ARRDC3 in ovarian cancer using GEPIA, ONCOMINE, GEO, and Kaplan-Meier Plotter databases for training and validation. Then, we conducted a stratified analysis for clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
2
2
1
Order By: Relevance
“…Meanwhile, using GSEA, we again confirmed that ARRDC2 was highly and consistently enriched in immune-related signaling pathways. Studies have shown that ARRDC3, an important member of the ARRDC family, was closely related to immunity in epithelial ovarian cancer, which supports our research ( Chen et al, 2021 ). The above enrichment analysis suggested that ARRDC2 may play an oncogenic role in ovarian cancer by influencing immune factors in the tumor microenvironment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, using GSEA, we again confirmed that ARRDC2 was highly and consistently enriched in immune-related signaling pathways. Studies have shown that ARRDC3, an important member of the ARRDC family, was closely related to immunity in epithelial ovarian cancer, which supports our research ( Chen et al, 2021 ). The above enrichment analysis suggested that ARRDC2 may play an oncogenic role in ovarian cancer by influencing immune factors in the tumor microenvironment.…”
Section: Discussionsupporting
confidence: 92%
“…A great many studies have shown that genes in the ARRDC family contributed to the progression of various malignancies such as gastric, cervical and colorectal cancers, and were strongly associated with poor prognosis ( Shen et al, 2018 ; Xiao et al, 2018 ; Takeuchi et al, 2019 ). For instance, ARRDC3, a member of the ARRDC family, served as a biomarker for the diagnosis and prognosis of epithelial ovarian cancer ( Chen et al, 2021 ). From this, it can be boldly speculated that ARRDC2 may likewise act as an oncogene in ovarian cancer and lead to poor prognosis, but its possible oncogenic mechanisms need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, using GSEA, we again con rmed that ARRDC2 was highly and consistently enriched in immune-related signaling pathways. Studies have shown that ARRDC3, an important member of the ARRDC family, was closely related to immunity in epithelial ovarian cancer, which supports our research (16). The above enrichment analysis suggested that ARRDC2 may play an oncogenic role in ovarian cancer by in uencing immune factors in the tumor microenvironment.…”
Section: Discussionsupporting
confidence: 88%
“…A great many studies have shown that genes in the ARRDC family contributed to the progression of various malignancies such as gastric, cervical and colorectal cancers, and were strongly associated with poor prognosis (13)(14)(15). For instance, ARRDC3, a member of the ARRDC family, served as a biomarker for the diagnosis and prognosis of epithelial ovarian cancer (16). From this, it can be boldly speculated that ARRDC2 may likewise act as an oncogene in ovarian cancer and lead to poor prognosis, but its possible oncogenic mechanisms need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…It is speci cally involved in the degradation and regulation of PAR1 via ALIX in triple-negative breast cancer [12]. ARRDC3 also suppresses tumor metastasis in other cancers [35][36][37][38][39]. In the present study, no signi cant results were obtained for p16-positive oropharyngeal cancer specimens.…”
Section: Discussioncontrasting
confidence: 59%